High prevalence of haplorchiasis in nan and Lampang Provinces, Thailand, proven by adult worm recovery from suspected opisthorchiasis cases - Adulsak Wijit (2018)
Opisthorchiasis, a risk factor for cholangiocarcinoma in humans, is of public health importance in Thailand. The Annual Surveillance Reports from Nan and Lampang Provinces, Thailand, for the year 2011 showed an opisthorchiasis prevalence of over 70% by recovery of eggs in the feces. This study investigated whether most cases are actually due to minute intestinal flukes (MIF) rather than Opisthorchis viverrini, as the eggs of both can hardly be differentiated by morphology. Fifty and 100 cases from residents in Nan and Lampang, respectively, had stools positive for eggs initially assumed to be those of O. viverrini. Each patient was given praziquantel at 40 mg/kg in a single dose. After 2 hr, 30-45 ml of the purgative magnesium sulfate was given, and stools were collected up to 4 times sequentially. The stools were examined for adult worms by simple sedimentation. It was found that 39 of 50 cases (78.0%) from Nan Province had Haplorchis taichui, with intensities ranging from 5 to 1,250 with an average of 62 worms/case. Taenia saginata (7 cases) and Enterobius vermicularis (1 case) were other helminths recovered as the co-infectants. In Lampang Province, H. taichui was recovered from 69 cases (69.0%). The number of flukes recovered ranged from 1 to 4,277, with an average of 326 worms/case. Four cases had Phaneropsolus bonnei, and 10 T. saginata as the co-infectants. Adult specimens of O. viverrini were not recovered from any stool. Clearly, MIF infection, especially haplorchiasis, is more common in northern Thailand. These findings should encourage the Public Health Office to employ more specific tools than Kato's method for surveillance of opisthorchiasis in Thailand. © 2013, Korean Society for Parasitology and Tropical Medicine.